Central venous catheters and arrhythmia: Two unusual cases. Issue 2 (March 2021) - Sosa Barrios, R Haridian; Lefroy, David; Ashby, Damien; Duncan, Neill
Jugular Tesio lines (TesioCaths; MedCOMP, Harleysville, PA, USA) are frequently used as permanent vascular accesses in haemodialysis patients. During the insertion procedure, arrhythmias are a relatively common complication, usually related to an excessively advanced catheter tip, without major consequences. We present two cases of life-threatening arrhythmias triggered by the Tesio catheter eccentric high-velocity jet of blood resolved after reposition of the catheter without further episodes, despite both lines being inserted under real-time ultrasound and fluoroscopic guidance. We believe dialysis lines should be checked for tip position even when long-standing to prevent relevant complications due to catheter sliding.